Out of pocket and catastrophic health expenditure in Tanzania: recent evidence on the incidence, intensity and distribution - John Massito; Gabriel Hinju (BMC Health Services Research)
Abstract Background In most low-income countries (LICs), health is mainly financed by out-of-pocket (OOP) expenditures. However, it is claimed that this form of payment causes a massive burden on poor households. This study investigates the catastrophic impact of out-of-pocket health expenditure by estimating the levels, intensities and distribution of catastrophic health expenditure among households in Tanzania. Methods The study applied the Wagstaff & va-Doorslaer methodology to measure the incidence and intensity of catastrophic expenditure and the concentration index to measure the distribution of catastrophic expenditure using panel data 2020/2021. Then descriptive-analytical methods such as frequencies, means, and proportions were used to report the results. Results The study found that 21.9% (19.1% from rural and 24.6% from urban) of the respondents reported visiting a healthcare facility within four weeks before the survey. Over 50% (53.5% from rural and 57.4% from urban) reported an incidence of illness or injury within the same period. The study also found that among those who utilised health care, about 7.1% (8.4% from rural and 5.7% from urban areas) experienced catastrophic health expenditures. The concentration index (-0.0175 and -0.0638) show that poor households are more likely to experience catastrophic health costs than rich households given the negative values of the indices. This phenomenon is particularly visible in Tanzania, where health insurance is still in its early stages of development. Conclusion We conclude that out-of-pocket health expenditures tend to lead to financial catastrophe for poor households, thereby exposing them to more poverty and forcing them to resort to coping mechanisms that compromise their welfare. This necessitates the development of new and reinforced existing systems to protect impoverished households against out-of-pocket and catastrophic healthcare costs.